Assessment of the availability and rationality of unregistered fixed dose drug combinations in Nepal: a multicenter cross-sectional study - Arjun Poudel; Mohamed Izham Mohamed Ibrahim; Pranaya Mishra; Subish Palaian (BMC, 2017)
Abstract Background The medications that are registered and available in a country are meant for the prevention and treatment of ailments and diseases. However, a lack of effective regulatory bodies and operative control mechanisms, especially in developing countries, promotes irrational and inappropriate use of medicines. This study aims to evaluate the availability and rationality of unregistered fixed-dose drug combinations (FDCs) in Nepal. Methods A snowball sampling method with visits to 20 retail pharmacies in each of five major cities in Nepal was used to assess the availability of unregistered FDCs. To justify the rationality of the FDCs obtained from these five cities, the toolkit developed by Health Action International Asia-Pacific (HAI-AP) was used. Results Altogether, 41 unregistered FDCs were obtained from the five cities. Among the total 41 FDCs, a majority were anti-inflammatory/analgesic/antipyretics. A maximum of eight drugs and a minimum of two drugs per combination were present among the total 41 FDCs, with a majority in the form of tablets followed by suspensions. The cost ranges from a minimum of 3.7 Nepalese Rupees (NRs) (= USD 0.05) to a maximum of 240 NRs (= USD 3.15). None of the FDCs fulfilled all the fundamental requirements as stated in the toolkit; thus, they were categorized as 'irrational'. Conclusions Unregistered FDCs are available in the Nepalese pharmaceutical market. All the unregistered FDCs found in our study were 'irrational' as per the HAI-AP toolkit. Regulatory authorities should initiate strict monitoring and appropriate regulatory mechanisms to prohibit the use of unregistered and irrational FDCs.